LEADERSHIP TRANSFORMATIONAL DAN KOMITMEN ORGANISASIONAL TERHADAP PRESTASI PESERTA PADA BALAI PELATIHAN VOKASI DAN PRODUKTIVITAS (BPVP) PADANG KEMENTERIAN KETENAGAKERJAAN REPUBLIK INDONESIA - Muhammad Taufik; Henryanto Abaharis (Jurnal Bina Bangsa Ekonomika, 2024)
The purpose of this research is to determine the influence of transformational leadership and organizational commitment variables on the participant achievements at the Vocational Training and Productivity Center (BPVP) Padang, Ministry of Manpower of the Republic of Indonesia. This research method employs a quantitative approach. Data collection techniques involve distributing questionnaires to 91 respondents using probability sampling. Respondents' answers are processed using SPSS. The results of this research indicate that transformational leadership and organizational commitment have a positive and significant impact on the participants' performance at the Vocational Training and Productivity Center (BPVP) Padang, Ministry of Manpower of the Republic of Indonesia